Participation of the IGF system in the pathogenesis of bovine cystic ovarian disease (FAVE Sección Ciencias Veterinarias, 2016)
Cystic ovarian disease (COD) is one of the most frequent reproductive disorders in dairy cows. Their development is associated with an imbalance in the hypothalamus-hypophyseal-gonadal axis in which endocrine factors, including insulin like growth factor (IGF) system, are involved in follicular development, cell differentiation and secretion ovarian hormones. Considering that the IGF system is an important regulator of the follicular growth and functionality, we have evaluated the involvement of members of the IGF system in the COD development. Alterations in different components of the IGF system could modify the normal ovarian function and participate in the development of the COD in cattle.
Keywords: insuline like growth factor system; cystic ovarian disease; cow